2017
DOI: 10.15420/aer.2017:10:1
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Future for Remote Cardiac Implantable Electronic Device Management?

Abstract: Remote follow-up and monitoring of patients implanted with cardiac implantable electronic devices (CIEDs) has been introduced over a decade ago, and is now indicated according to European (class IIa indication 1 ) and American (class I indication 2 ) guidelines. There have been high expectations that this technology will improve patient outcome, as it significantly shortens response to actionable events (e.g. AF) compared with standard in-office follow-up. 3,4 However, several randomised trials have failed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Debates on the optimal telemonitoring technology (parameters to be monitored, frequency of data transmission) and clinical response system continue [11, 26, 3638]. Both randomized trials of implant-based telemonitoring with positive outcomes, IN-TIME [9] and CHAMPION [31, 32], were characterized by largely successful daily data transmission and a well-designed response system to device-mediated alerts [26, 39].…”
Section: Discussionmentioning
confidence: 99%
“…Debates on the optimal telemonitoring technology (parameters to be monitored, frequency of data transmission) and clinical response system continue [11, 26, 3638]. Both randomized trials of implant-based telemonitoring with positive outcomes, IN-TIME [9] and CHAMPION [31, 32], were characterized by largely successful daily data transmission and a well-designed response system to device-mediated alerts [26, 39].…”
Section: Discussionmentioning
confidence: 99%
“…In a subgroup analysis, device type and essential patient characteristics did not interact with the overall neutral result. It was concluded that in developed healthcare systems with high quality HF services, using data from weekly RM of CIEDs is unlikely to improve patient outcomes 34 , 60 …”
Section: Recent Randomized Trialsmentioning
confidence: 99%
“…To better understand why overall results differed between Truecoin and the REM-HF trial, 34 we compared operational details. Five major differences emerge: (i) Truecoin included only daily RM, while REM-HF excluded this approach; (ii) in REM-HF, there was no true control group with IPE alone, because control patients were permitted to continue with alert-based RM if this was already in place 60 ; (iii) REM-HF required weekly RM transmissions to be actively performed by the patients and almost 40% of patients transmitted data for <75% of weeks 60 ; this attrition in compliance degraded connectivity, i.e. the foundation for RM, in contrast to successful transmission on >85% of days in Truecoin consistently during follow-up 8 , 9 , 23 , 31–33 , 39 .…”
Section: Daily Remote Monitoring: Truecoin and Comparisons With Rem-hfmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 , 2 Despite these advancements, remote follow-up still follows a calendar-based schedule, imparting significant review burden on staff and resulting in few meaningful actions. 3 , 4 To further improve patient outcomes, many CIED systems now provide exception-based remote monitoring approaches, using alerts to notify physicians of significant clinical changes sensed by the device or of CIED performance issues. 5 However, device connectivity is critical for the operation of the alert-based system and thus remains as a substantial barrier to unlocking its full effectiveness.…”
Section: Introductionmentioning
confidence: 99%